A Survey of Music Recommendation System for old age people - Das, Samya; Dey, Soham; Jana, Radha Krishna (International Journal of Computer Sciences and Engineering, 2026)
One of the most fruitful forms of media is music since it can evaluate strong emotions and marshal listeners with subliminal instructions. It manipulates our feelings, which in turn affects how we feel. Books, movies, and television are a few other ways to communicate, but music communicates its message in just a few brief seconds. It can encourage us and help us when we are down. We frequently experience a mood when listening to depressing music. We experience happiness when we listen to music. Many Internet businesses have looked for using sentiment analysis to recommend content that is in keeping with the human emotions that are represented in informal texts posted on social networks. Here we propose a music recommendation methodology.